Effect of the Basic Electrochemical Cell Operating Parameters on the Performance of the Electrolysis of Kraft Pulping Black Liquor. (25th October 2017) - Cloutier, Jean-Noël; Savadogo, Oumarou; Paris, Jean; Perrier, Michel; Labrecque, Raynald; Kandev, Nedeltcho; Champagne, Pascal
Abstract : The biorefinery initiative in the pulp and paper industry aims at diversifying its product offering to include value-added biomaterials from lignin. We have developed an electrochemical technique to precipitate lignin from black liquor and simultaneously recover caustic soda. Our approach, which is based on the electrolysis of black liquor, reduces its alkalinity electrochemically to the point of lignin precipitation. It does not require chemicals from an external source and does not generate additional effluents. The technology entails an increased pulp production for Kraft pulp mills that are limited by their recovery boiler capacity or their causticizing system. In this study, we investigated the effect of various basic operating parameters of on the performance of the electrolysis of black liquor; in particular the electrochemical reactions taking place in the cell, the current density distribution and the contribution of individual cell components to the total voltage of the electrochemical reactor.